Uncovering DELLA-Independent Gibberellin Responses by Characterizing New Tomato procera Mutants. Issue 6 (2nd June 2015) - Livne, Sivan; Lor, Vai S.; Nir, Ido; Eliaz, Natanella; Aharoni, Asaph; Olszewski, Neil E.; Eshed, Yuval; Weiss, David
Abstract : A loss-of-function mutation in the single tomato DELLA gene PROCERA revealed DELLA-related phenotypes and facilitated the identification of DELLA-independent gibberellin responses. Abstract: Gibberellin (GA ) regulates plant development primarily by triggering the degradation/deactivation of the DELLA proteins. However, it remains unclear whether all GA responses are regulated by DELLAs. Tomato ( Solanum lycopersicum ) has a single DELLA gene named PROCERA ( PRO ), and its recessive pro allele exhibits constitutive GA activity but retains responsiveness to external GA . In the loss-of-function mutant pro ΔGRAS, all examined GA developmental responses were considerably enhanced relative to pro and a defect in seed desiccation tolerance was uncovered. As pro, but not pro ΔGRAS, elongation was promoted by GA treatment, pro may retain residual DELLA activity. In agreement with homeostatic feedback regulation of the GA biosynthetic pathway, we found that GA20oxidase1 expression was suppressed in pro ΔGRAS and was not affected by exogenous GA3 . In contrast, expression of GA2oxidase4 was not affected by the elevated GA signaling in pro ΔGRAS but was strongly induced by exogenous GA3 . Since a similar response was found in Arabidopsis thaliana plants with impaired activity of all five DELLA genes, we suggest that homeostatic GA responses are regulated by both DELLA-dependent and -independent pathways. Transcriptome analysis of GA -treated pro ΔGRAS leaves suggests that 5% of all GA -regulated genes in tomato are DELLA independent.